2008
DOI: 10.1016/j.molcel.2008.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Ezh1 and Ezh2 Maintain Repressive Chromatin through Different Mechanisms

Abstract: Polycomb group proteins are critical to maintaining gene repression established during Drosophila development. Part of this group forms the PRC2 complex containing Ez that catalyzes methylation of histone H3 lysine 27 (H3K37me2/3), marks repressive to transcription. We report that the mammalian homologs Ezh1 and Ezh2 form similar PRC2 complexes but exhibit contrasting repressive roles. While PRC2-Ezh2 catalyzes H3K27me2/3 and its knockdown affects global H3K27me2/3 levels, PRC2-Ezh1 performs this function weak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

59
791
3
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 773 publications
(856 citation statements)
references
References 70 publications
59
791
3
3
Order By: Relevance
“…There is large overlap in the set of genes that retain H3K27me3 between ES cells and AML leukemic cells, and almost all of these genes are documented Ezh1 targets. Ezh1 is the only other known methyltransferase besides Ezh2 to catalyze the trimethylation of H3K27 (16,32). The ability of Ezh1 to compensate for Ezh2 inactivation in cancer appears to be context dependent (30).…”
Section: Discussionmentioning
confidence: 99%
“…There is large overlap in the set of genes that retain H3K27me3 between ES cells and AML leukemic cells, and almost all of these genes are documented Ezh1 targets. Ezh1 is the only other known methyltransferase besides Ezh2 to catalyze the trimethylation of H3K27 (16,32). The ability of Ezh1 to compensate for Ezh2 inactivation in cancer appears to be context dependent (30).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this observation, Ezh2 is required for early mouse development. The two proteins show functional complementation but don't appear to be completely redundant, since Ezh1 can't rescue the pluripotency defects observed in EZH2 À/À embryonic stem cells (Margueron et al, 2008). Ezh2 À null mouse embryos die during the transition from pre-to post-implantation development (O'Carroll et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…A schematic representation of the components of PRC1 and PRC2 is illustrated in Figure 1. The main components of PRC1 and PRC2 in Drosophila, mouse and human are summarized in Table 1 (Laible et al, 1999;O'Carroll et al, 2001;Margueron et al, 2008) Ezh1 and Ezh2 (Margueron et al, 2008) SET domain, CXC domain and homology domains I and II…”
Section: Components Of Polycomb Complexesmentioning
confidence: 99%
“…DNA-binding factors and CpG islands are two main features involved in the recruitment of Pc complexes to chromatin, particularly on PREs (Gal-Yam et al, 2008;Meissner et al, 2008;Mendenhall et al, 2010). Nucleosomal array analyses have shown that Pc components are able to remodel chromatin structure and compact chromatin independently of histone modifications (Eskeland et al, 2010;Francis et al, 2004;Margueron et al, 2008). PRC1 inhibits transcription at the promoter region of the targeted gene through chromatin remodeling (Lavigne et al, 2004), although this conclusion is controversial (Eskeland et al, 2010).…”
Section: Recruitment Of Polycomb Complexesmentioning
confidence: 99%